2022
DOI: 10.3389/fnbeh.2022.931964
|View full text |Cite
|
Sign up to set email alerts
|

Encore: Behavioural animal models of stress, depression and mood disorders

Abstract: Animal studies over the past two decades have led to extensive advances in our understanding of pathogenesis of depressive and mood disorders. Among these, rodent behavioural models proved to be of highest informative value. Here, we present a comprehensive overview of the most popular behavioural models with respect to physiological, circuit, and molecular biological correlates. Behavioural stress paradigms and behavioural tests are assessed in terms of outcomes, strengths, weaknesses, and translational value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 541 publications
0
19
0
Order By: Relevance
“…120 Interestingly, there are animal models that study, for example, chronic stress corresponding to a human being's daily unpleasant situations at work or an abusive job or prolonged disturbances in daily life. 114 It is important to highlight that there are HMs used in clinical practice for the consequences of different daily life stressors, some of them suffered for long periods of time ( Natrum muriaticum for example). 63 The Homeopathic Repertory includes a specific rubric named “ailments from…” (admonition; violence; accusations; lack of affection; deceived friendship; disappointed love; anxiety; not being appreciated; anticipation; punishment; anger; indignation; overwork; and so on).…”
Section: Future Directionsmentioning
confidence: 99%
“…120 Interestingly, there are animal models that study, for example, chronic stress corresponding to a human being's daily unpleasant situations at work or an abusive job or prolonged disturbances in daily life. 114 It is important to highlight that there are HMs used in clinical practice for the consequences of different daily life stressors, some of them suffered for long periods of time ( Natrum muriaticum for example). 63 The Homeopathic Repertory includes a specific rubric named “ailments from…” (admonition; violence; accusations; lack of affection; deceived friendship; disappointed love; anxiety; not being appreciated; anticipation; punishment; anger; indignation; overwork; and so on).…”
Section: Future Directionsmentioning
confidence: 99%
“…In this context, preclinical research is essential for connecting theoretical knowledge with clinical data by exploring various paradigms, such as genetic models, acute/chronic stress models, brain neurotransmitters/specific brain injury models, and models induced by pharmacological interventions [ 35 , 36 , 37 , 38 ]. Although none of these models completely reproduce human MDD (i.e., face validity, construct validity, and predictive validity are still far from being perfect), they are considered relevant because of their capacity to mimic certain features of this pathological condition and thus allowing for the systematic investigation of etiology, pathogenesis, and treatment of depression [ 36 , 39 ]. For example, the antidepressant effects of kynurenic acid, an L-tryptophan metabolite with neuromodulatory activities, have been explored in preclinical studies [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study showed that the antidepressant effects of kynurenic acid are modeled by this pathway’s interactions with GABA-ergic (through GABA-A receptors), dopaminergic (i.e., D2, D3, and D4 receptors), and serotonergic (i.e., 5-HT2 receptors) neurotransmission [ 40 ]. The stress vulnerability model has been proven useful in separating depressive-like and anxious-like phenotypes during benzodiazepine administration in mice; this model has further supported the utility of brain-derived neurotrophic factor (BDNF) in developing neural and behavioral plasticity and the effects of antidepressants [ 39 , 41 ]. The chronic unpredictable mild stress model is another robust tool for the pharmacological research of MDD, and various antidepressants have been explored using this paradigm; for example, antidepressant-induced reduction in hippocampal cytogenesis has been correlated with symptoms amelioration in a study investigating the effects of escitalopram in rats with this chronic stress model [ 39 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic social defeat stress (CSDS) is a robust and widely used chronic stress model that induces depression-like and PTSD-like symptoms in a subset of exposed rodents (46,47). Experimental mice exhibiting social avoidance are deemed “stress-susceptible”, while those that do not are “stress-resilient” (48).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic social defeat stress (CSDS) is a robust and widely used chronic stress model that induces depression-like and PTSD-like symptoms in a subset of exposed rodents (46,47).…”
Section: Introductionmentioning
confidence: 99%